(untitled) (Conferencea, 2023)
While a clinical trial was carried out during the data collection phase, higher incidences of dental caries were recorded in patients. In this regard, it was decided to evaluate only the intensity. In our study, the KP O index was also used to evaluate the intensity of dental caries, which represents a quantitative assessment. Indicators of career intensity in T-planted patients. In order to study in detail, the intensity of tooth caries in between, the patients included in the study were analyzed in each of the cross-groups and groups. To do this, the value in each group was determined clinical symptoms of cariosis lesions (cariosis, filled and extracted teeth). The data are presented in Tables 1and 2 and Figures 1. Evaluation of the intensity indicators of carivalic lesions within the group for patients is divided according to gender. Indicators of the intensity of the cariosis process in patients in Group 1